Development Of A Colour-Changing Patch To Detect Temperature Fluctuation - Ghosh, Anindita (My University, 2023)
It is not possible to visually determine if a drug has degraded or been exposed to high temperatures because degradation is not related to its expiration date. Therefore, there is a need to create a product that can differentiate visibly between degraded drugs and others. In this study, we are developing a cost-effective patch that can detect temperature fluctuations and be placed on top of the drug label. The patch will be pH-sensitive and temperaturesensitive, changing color when exposed to higher temperatures. This color change will help distinguish degraded drugs from others. The experiment involves simple chemical reactions, including the absorption of evaporated water and the detection of pH changes by a pH indicator. The setup consists of four layers: a hydrogel layer to absorb water, NaOH paper, a thymol blue patch, and a wax slack layer separating the first two layers. When the setup is exposed to high temperatures, water evaporates from the hydrogel layer and is absorbed by the NaOH paper. This causes both the NaOH paper and the thymol blue patch to become wet, resulting in a pH change that changes the color from yellow to blue. As a waste paper management strategy, extracted cellulose from office waste paper is used to synthesize CMC hydrogel blend as a water absorbent layer.
Keywords: Heat Sensing; Thermal Marker; Chemical Marker; Indicator; Color changing Patch; Conditional release; Temperature flactuation detection device for low tempareture